Financial Analysis for the Temporary Social Security Regime Regarding Old Age, Disability and Death for State Workers in Timor-Leste - World Bank (Washington, DC, 2015)
This report was prepared by the World Bank at the request of the Government of Timor-Leste, and is used to assist the government with short-term budgeting and understanding the long-term dynamics of its new pension program. It summarizes findings regarding the financial and actuarial status of Timor-Leste's pension program for civil servants, the quot;Temporary Social Security Regime Regarding Old Age, Disability and Death for State Workers.quot; Timor-Leste is expecting rapid population growth over the next 75 years. The growth of the population, decentralization, and the expected transition to a middle-income country will drive the need for a growing number of future civil servants. Section I briefly summarizes the legal environment and the provisions of the pension program for civil servants. Section II summarizes the results of the analysis and estimates the cost of the program on a pay-as-you-go basis with payments from the budget, and on a funded basis with contributions as a percent of payroll. Section III discusses the sources of the input data and the methods used to prepare the data for use in this valuation. Section IV summarizes the macroeconomic and demographic assumptions used to prepare this valuation report. Section V comments on some of the non-standard design features of the pension program. Finally, Section VI summarizes the team's findings and discusses the next steps required in the implementation of the civil service pension program.